The Role of miR-18b in MDM2-p53 Pathway Signaling and Melanoma Progression - Dar, Altaf A (Oxford University Press, 2013)
BACKGROUND: Although p53 is inactivated by point mutations in many tumors, melanomas infrequently harbor mutations in the p53 gene. Here we investigate the biological role of microRNA-18b (miR-18b) in melanoma by targeting the MDM2-p53 pathway. METHODS: Expression of miR-18b was examined in nevi (n = 48) and melanoma (n = 92) samples and in melanoma cell lines and normal melanocytes. Immunoblotting was performed to determine the expression of various proteins regulated by miR-18b. The effects of miR-18b overexpression in melanoma cell lines were investigated using assays of colony formation, cell viability, migration, invasion, and cell cycle and in a xenograft model (n = 10 mice per group). Chromatin immunoprecipitation and methylation assays were performed to determine the mechanism of microRNA silencing. RESULTS: Expression of miR-18b was substantially reduced in melanoma specimens and cell lines by virtue of hypermethylation and was reinduced (by 1.5- to 5.3-fold) in melanoma cell lines after 5-AZA-deoxycytidine treatment. MDM2 was identified as a target of miR-18b action, and overexpression of miR-18b in melanoma cells was accompanied by 75% reduced MDM2 expression and 2.5-fold upregulation of p53, resulting in 70% suppression of melanoma cell colony formation. The effects of miR-18b overexpression on the p53 pathway and on melanoma cell growth were reversed by MDM2 overexpression. Stable overexpression of miR-18b produced potent tumor suppressor activity, as evidenced by suppressed melanoma cell viability, induction of apoptosis, and reduced tumor growth in vivo. miR-18b overexpression suppressed melanoma cell migration and invasiveness and reversed epithelial-to-mesenchymal transition. CONCLUSIONS: Our results demonstrate a novel role for miR-18b as a tumor suppressor in melanoma, identify the MDM2-p53 pathway as a target of miR-18b action, and suggest miR-18b overexpression as a novel strategy to reactivate the p53 pathway in human tumors.